The Impact of Financial Crises on Foreign Direct Investment: Evidence from Developed Countries. - Liu, Xiaoxue (2012)
The purpose of this paper is to analyze the impact of financial crises on foreign direct investment (FDI) activity. The paper will examine whether or not there is fire sale FDI in host countries during a financial crisis. Also, it explores the extent to which FDI inflows is affected by the occurrence of a financial crisis. The paper adds a detail about the types of financial crises. It is expected that different types of financial crises have varying effects on FDI inflows. Hence, financial crises are categorized into banking crisis, inflation crisis, and currency crisis. It is also expected that differing types of FDI have different reaction to financial crises, hence FDI inflows are distinguished between two groups including cross-border merger and acquisitions (M&A) and greenfield investment. The sample used in this paper is based on 23 developed countries across four economic regions for the period 1990-2010. The paper uses a panel data analysis to check the appropriateness and effectiveness of financial crises in the FDI regression model. The empirical results indicate that financial crises have strong negative effects on FDI activity in my sample. In particular, banking crisis and currency crisis are shown to reduce the value of FDI inflows, FDI stocks and greenfield FDI activities significantly, while inflation crisis has little impact FDI activity. I do not find evidence in supporting the fire sale FDI hypothesis in my sample. On the other hand, financial crises lead to large decline in the value of cross-border M&A. Keywords: Foreign direct investment (FDI), Fire sale FDI, Financial crises, cross-border Merger and acquisitions (M&A)